TUNISHA SHARMA’S LAST CAPTION ‘‘THOSE WHO ARE DRIVEN BY THEIR PASSION DOESN’T STOP’’- AN IRONY, IN HER SUCIDIAL MURDER MYSTERY- INVOKING A DEBATE ON LOSS OF LOVE IN RELATIONSHIPS (Contemporary Journal of Social Science Review, 2025)
The intent of this research paper is to elaborate the factors leading to the tragic suicidal murder mystery of a rising Indian television and film actress Tunisha Sharma. Who at the age of twenty took her life by attempting suicide- through hanging herself on 24 December 2022, in a studio in Naigaon, Maharashtra, Tunisha Sharma hanged herself in the make-up room of co-star Sheezan Khan on the set of the TELEVISION SERIAL ALI BABA: DASTAAN-E-KABUL CHAPTER 1. She was taken to a hospital where she was declared dead on arrival (DOA). Her last Instagram post was on the same day when she took her life with an ironic caption ‘‘THOSE WHO ARE DRIVEN BY THEIR PASSION DOESN’T STOP’’ which leads to a heated argument towards her love affair with her costar, Mr. Sheezan Khan. The purpose of this research is to elaborate those factors, which causes psychological disturbance in the teenagers due to the disturbance in their love affairs and harsh breakups.